Interaction of Protease-Activated Receptor 2 with G Proteins and β-Arrestin 1 Studied by Bioluminescence Resonance Energy Transfer - Ayoub, Mohammed Akli; Pin, Jean-Philippe R. (Frontiers in Endocrinology, 2013)
G protein-coupled receptors (GPCRs) are well recognized as being able to activate several signaling pathways through the activation of different G proteins as well as other signaling proteins such as beta-arrestins. Therefore, understanding how such multiple GPCR-mediated signaling can be integrated constitute an important aspect. Here, we applied bioluminescence resonance energy transfer (BRET) to shed more light on the G protein coupling profile of trypsin receptor, or protease-activated receptor 2 (PAR2), and its interaction with beta-arrestin1. Using YFP and Rluc fusion constructs expressed in COS-7 cells, BRET data revealed a pre-assembly of PAR2 with both Galphai1 and Galphao and a rapid and transient activation of these G proteins upon receptor activation. In contrast, no preassembly of PAR2 with Galpha12 could be detected and their physical association can be measured with a very slow and sustained kinetics similar to that of beta-arrestin1 recruitment. These data demonstrate the coupling of PAR2 with Galphai1, Galphao and Galpha12 in COS-7 cells with differences in the kinetics of GPCR-G protein coupling, a parameter that very likely influences the cellular response. Moreover, this further illustrates that preassembly or agonist-induced G protein interaction depends on receptor-G protein pairs indicating another level of complexity and regulation of the signaling of GPCR-G protein complexes and its multiplicity.